2018
DOI: 10.1111/nep.12951
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis in patients with failed kidney transplant: Single centre experience

Abstract: Our study found a small but significantly higher rate of PD technique failure in the post-transplant cohort, but this did not appear to be related to peritonitis rates or peritoneal membrane function. Further studies are required to explore reasons for PD technique failure in patients who have had kidney transplant, but our study supports the use of PD in selected patient from this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
2
10
0
2
Order By: Relevance
“…Animal studies have indicated that long-term exposure to immunosuppressant therapy (calcineurin inhibition) can lead to fibrosis of the peritoneal membrane [34]. However, in one of the studies included in our review, Chaudhri et al [23] demonstrated similar baseline dialysate-toplasma ratios of creatinine and net ultrafiltration between the two study groups indicating a limited role for long term calcineurin inhibitors on the peritoneal membrane function in patients with kidney transplant.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Animal studies have indicated that long-term exposure to immunosuppressant therapy (calcineurin inhibition) can lead to fibrosis of the peritoneal membrane [34]. However, in one of the studies included in our review, Chaudhri et al [23] demonstrated similar baseline dialysate-toplasma ratios of creatinine and net ultrafiltration between the two study groups indicating a limited role for long term calcineurin inhibitors on the peritoneal membrane function in patients with kidney transplant.…”
Section: Discussionmentioning
confidence: 80%
“…A separate group of two studies reported higher mortality in the Tx group than in the nTx group. Chen et al [21] found a borderline higher incidence of peritonitis in the Tx group than in the nTx group, while Chaudhri et al [23] found a lower risk of peritonitis in the Tx group. Five studies reported the time-to-first peritonitis episode with four of them finding no differences between the two groups, while Badve et al [18] found significantly longer times in the Tx group than in the nTx group.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the technique survival, in accordance with others [10,29], no difference was found between the groups in the present study. In contrast, Chaudhri et al found a higher rate of technique failure in patients coming from Tx compared to never-transplanted patients [12]. Yet Benomar et al have reported similar results, and pointed out that poor dialysis adequacy was the main cause of technique failure [7].…”
Section: Discussionmentioning
confidence: 95%
“…Considering peritonitis, Chen et al found a trend toward a lower event-free time in pediatric patients who started PD after Tx failure compared to those who were transplanted naïve [30]. However, studies on the adult population showed no difference regarding peritonitis between groups [7,9,12]. Notably, in those studies, different immunosuppressive protocols were performed after PD initiation, making a comparison between them difficult to analyze.…”
Section: Discussionmentioning
confidence: 99%